Entrepreneurial role models and college students’ entrepreneurial calling: A moderated mediation model - Jin, Dongmei; Liu, Xiaomeng; Zhang, Fuqin; Wen, Zhiyi (Frontiers in Psychology, 2023)
Based on the social learning theory, the theory of planned behavior and the entrepreneurial event model, this study examined the association between entrepreneurial role models and entrepreneurial calling of college students. Specifically, a moderated mediation model was developed to investigate the mediating association of entrepreneurial perceived behavioral control and the moderating association of entrepreneurial hands-on practice. Data were collected from a longitudinal survey of 519 Chinese college students. Using hierarchical regression, support was found for both mediation and moderation association. Results showed that entrepreneurial role models were positively associated with college students' entrepreneurial calling by partially mediating with entrepreneurial perceived behavioral control. Moreover, Entrepreneurial hands-on practice not only moderated the positive relationship between entrepreneurial perceived behavioral control and entrepreneurial calling, but also moderated the mediating association of entrepreneurial perceived behavioral control between entrepreneurial role models and entrepreneurial calling. This study contributes to promote the cultivation of college students’ entrepreneurial calling.